Microsurgical Anatomy of Middle Cerebral Artery in Northwest Indian Population: A Cadaveric Brain Dissection Study - Rakshith, Srinivasa; Shweta, Kedia; Pravin, Salunke; Daisy, Sahni; Eilene, Basu; Kumar, Krishnakutty Muthiraklayil Sareesh; Mathuriya, Suresh Narain (Asian Journal of Neurosurgery, 2024)
The introduction of cadaveric dissection of cerebral vasculature as a part of the neurosurgical training module would help the neurosurgical residents to understand the complex neuroanatomy of the brain vasculature and help gain confdence during the surgical procedure.To the best of our knowledge microsurgical anatomical studies of theMCA have not been done among the Northwest Indian population. Anatomical variations of MCA that have not been described before may come in as a surprise during any surgical intervention. Hence, we intend to record the anatomical variations of the MCA anatomy and its implications in contemporary vascular surgery and neurosurgical practice. The objective of this work was to study and compare the microsurgical anatomy and variations of MCA in Northwest Indian cadavers with the available literature.
Keywords: Middle Cerebral Artery; Cadaveric Dissection; Neuroanatomy